Antecedentes e características do risco de fraude contábil: uma análise multicasos no setor bancário brasileiro - Borges, Sabrina Rafaela Pereira (2017)
This study aims to investigate the possible variables related to the risk of accounting fraud in three Brazilian banks. In order to achieve this objective, the financial statements of three banking financial institutions were analyzed over a five-year period. After data collection, statistical techniques were carried out, using Kruskal Wallis test and the Student's t-test for independent samples through Bootstrap. Delphi technique was also used in three rounds with questionnaires with 21 experts to evaluate their opinion on the possible variables related to the risk of accounting fraud in banks. It can be inferred, after the analysis of the results, that Non-Current Asset accounts have characteristics that can contribute to the risk of bank fraud with statistical significance at the 5% level. In industry analysis, significant differences were found for the indicators of Net Margin, Loan Participation and Average Funding Cost. However, in individual analysis of the banks, there were significant differences for the Net Margin indexes for Bank C; Change in Shareholder’s Equity for Bank A and Participation of Loans in Bank B. In the opinion of experts, the variables of the internal and external environment are more related to the risk of accounting fraud in banking financial institutions than the nature of the accounts and the economic-financial indicators.